Central and Eastern Europe, 1944-1993 : detour from the periphery to the periphery - Berend, T. Iván (Tibor Iván), 1930- (Cambridge studies in modern economic history, 1996)
In this wide-ranging account, Ivan Berend traces the post-war fortunes of the countries lying between Germany and the former Soviet Union. Professor Berend draws both on his academic expertise and personal involvement in many of the events which he describes to produce a synthesis of a huge array of materials. His study stretches beyond the confines of economic history to provide insights into the complex interplay of ideological, social and political forces in the 'Eastern Bloc' countries over the last fifty years of revolutionary change. In particular Berend's analysis of totalitarianism, the development of nationalism, and the personalities at the centre of political life in eastern Europe offers an alternative perspective on the economies of the state-socialist regimes at the periphery of the western industrialised world.